2015
DOI: 10.1097/01.j.pain.0000460321.72396.88
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation-sensitive nociception involved in endometriosis-associated pain

Abstract: Endometriosis is a disease characterized by the growth of endometrial tissue outside the uterus and is associated with chronic pelvic pain. Peritoneal fluid (PF) of women with endometriosis is a dynamic milieu, rich in inflammatory markers and pain-inducing prostaglandins PGE2/PGF2α and lipid peroxides, and the endometriotic tissue is innervated with nociceptors. Our clinical study showed the abundance of oxidatively-modified lipoproteins in the PF of women with endometriosis and the ability of antioxidant sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 80 publications
3
38
0
Order By: Relevance
“…Onalan G et al [138] Animal study Significant decreases in the mean implant areas and significant decreases in serum and peritoneal TNF-a levels NAC elevates GSH levels and improves the toxic effects of ROS, a protection that is related to scavenging of free radicals Ray K et al [139] In vitro + Animal study (samples obtained from endometriosis patients)…”
Section: Inhibition Of the Intracellular Level Of Ros By Antioxidantmentioning
confidence: 98%
See 1 more Smart Citation
“…Onalan G et al [138] Animal study Significant decreases in the mean implant areas and significant decreases in serum and peritoneal TNF-a levels NAC elevates GSH levels and improves the toxic effects of ROS, a protection that is related to scavenging of free radicals Ray K et al [139] In vitro + Animal study (samples obtained from endometriosis patients)…”
Section: Inhibition Of the Intracellular Level Of Ros By Antioxidantmentioning
confidence: 98%
“…The authors reported that treatment with NAC as well as other anti-inflammatory and antioxidant drugs suppressed the pain-inducing capability of the lipoproteins. The proposed mechanism was that of an inhibition of oxidation of LDL by the treatment agents [139].…”
Section: N-acetyl-l-cysteinementioning
confidence: 99%
“…Since we recently identified that ox-LDLs parallel nociceptive responses similar to PF from women with endometriosis-associated pain [28], we hypothesized that these lipoprotein components function through modulating miRNAs that regulate inflammatory and nociceptive genes in endometriosis. We compared the miRNA profile of PF treated endometriotic cells to Ox-LDL treated cells.…”
Section: Introductionmentioning
confidence: 99%
“…Oxylipins are oxidized products of PUFA (Gabbs et al., ). Omega‐6 ( n ‐6)‐derived oxylipins tend to have increased inflammatory and vasoconstrictive effects, while n ‐3‐derived oxylipins tend to be anti‐inflammatory (Calder, ; Gabbs et al., ; Ray et al., ). It is unknown how the method of preparation affects the oxylipin content of fish fillets and the potential health impact of those oxylipins.…”
Section: Introductionmentioning
confidence: 99%